Fractal approach to the identification of complex systems - Bol’shakov, V.I.; Volchuk, V.M.; Dubrov, Yu.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
A possibility of applying the fractal models for the identification of complex systems is considered. An algorithm for determining the area of self-similarity of the object under consideration is presented. The algorithm allows one to reduce the probability of the object malfunctioning.